The relationship between paternalistic leadership and organization commitment at Jabatan Kerja Raya Melaka / Amirul Hazim Amir - Amir, Amirul Hazim (Faculty of Business and Management, 2018)
The relationship between paternalistic leadership and organization commitment. The purposes of conducted study at Jabatan Kerja Raya to minimize the problem of transfer in that company. The transfer intention one of the popular problem happened in that company due to the treatment by their employers. The study is to determine which leadership lead to the organization commitment. The study used questionnaire to collected the data from respondent that consist 120 employees of Kumpulan Pelaksana 2 that interact directly with the employer. The finding in this research shows the Benevolence dimension have strong relationship with organization commitment. This kind of leadership more to treat employees as part of family and suitable to used in that company compared to others dimension. Since the respondent between age 30-39 years old, pay high attention and have greater responsibility towards their family. The employees required employer that understand their situation and lenient.